Functional and Morphological Effects of Grape Seed Proanthocyanidins on Peripheral Neuropathy in Rats with Type 2 Diabetes Mellitus. (17th December 2013) - Ding, Ye; Dai, Xiaoqian; Jiang, Yanfei; Zhang, Zhaofeng; Li, Yong
<x xml:space="preserve">Abstract</x> Grape seed proanthocyanidins (GSPs) possess a broad spectrum of pharmacological and therapeutic properties. The aim of this study was to examine the effect of GSPs on functional and morphological abnormalities in the peripheral nerves of rats with type 2 diabetes mellitus. Diabetic rats were induced by two injections of 25 mg streptozotocin/kg body weight and 8 weeks of a high‐carbohydrate/high‐fat diet. GSPs were then administrated to the rats for 16 weeks. Thermal and mechanical sensitivity thresholds and nerve conductive velocity were measured to evaluate peripheral nerve function. Light microscopy was used with special stains to observe the morphological changes in the central and peripheral nervous systems. Calcium (Ca2+) homeostasis and ATPase activities in the sciatic nerves were also determined. In diabetic rats receiving GSP treatment (especially at the 500 mg/kg dose), the abnormal peripheral nerve function and impaired nervous tissues (L4 to L5 spinal cord segments, L5 dorsal root ganglion, and sciatic nerves) were improved to a significant extent. Moreover, 500 mg/kg GSP treatment significantly reduced the concentration of free Ca2+ and elevated Ca2+‐ATPase activity in sciatic nerves. These results suggest that GSPs may prevent early functional and morphological abnormalities in the peripheral nerves of rats with type 2 diabetes mellitus. Copyright © 2013 John Wiley & Sons, Ltd.